The Faddeev equation and essential spectrum of a model operator associated with the Hamiltonian of nonconserved number of particles - Muminov, Zahriddin; Ismail, Fudziah; Rasulov, Jamshid (Hindawi Publishing Corporation, 2014)
A model describing a truncated operator H (truncated with respect to the number of particles) and acting in the direct sum of zero-, one-, and two-particle subspaces of fermionic Fock space over is investigated. The location of the essential spectrum of the model operator H is described by means of the spectrum of the Friedreich model . Moreover, for the resolvent of H, the Faddeev type system of integral equations is obtained.